Sipa1 promoter polymorphism predicts risk and metastasis of lung cancer in Chinese2. Issue 1 (9th May 2013) - Xie, Chenli; Yang, Lei; Yang, Xiaorong; Yang, Rongrong; Li, Yinyan; Qiu, Fuman; Chen, Mei; Fang, Wenxiang; Bin, Xiaonong; Deng, Jieqiong; Huang, Dongsheng; Liu, Bin; et al.
Abstract Signal‐induced proliferation associated gene 1 (Sipa1) is a signal transducer to activate the Ras‐related proteins and modulate cell progression, differentiation, adhesion and cancer metastasis. In this study, we tested the hypothesis that single nucleotide polymorphisms (SNPs) in Sipa1 are associated with lung cancer risk and metastasis. Three common SNPs (rs931127A > G, rs2448490G > A, and rs3741379G > T) were genotyped in a discovery set of southern Chinese population and then validated the promising SNPs in a validation set of an eastern Chinese population in a total of 1559 lung cancer patients and 1679 cancer‐free controls. The results from the two sets were consistent, the rs931127GG variant genotype had an increased risk of lung cancer compared to the rs931127AA/GA genotypes (OR = 1.27; 95% CI = 1.09–1.49) after combination of the two populations, and the rs931127GG interacted with pack‐year smoked on increasing lung cancer risk (P = 0.037); this SNP also had an effect on patients' clinical stages (P = 0.012) that those patients with the rs931127GG genotype had a significant higher metastasis rate and been advanced N, M stages at diagnosis. However, these associations were not observed for rs2448490G > A and rs3741379G > T in the discovery set. Our data suggest that the SNP rs931127A > G in the promoter of Sipa1 was significantly associated with lung cancer risk and metastasis, which may be a biomarker to predict the risk and metastasis of lung cancer. © 2013 Wiley Periodicals, Inc.